Treatment of gastric adenocarcinoma at a New Zealand centre: meeting the challenges of a low volume country. Issue 1 (31st October 2019) - Saw, Kai Sheng; Robertson, Jason; Walsh, Michael; Hider, Phillip; Rodgers, Michael; Booth, Michael; Srinivasa, Sanket; Koea, Jonathan
Abstract: Background: Surgical treatment of gastric cancer in New Zealand is challenging because of a low annual incidence of 400 patients and population dispersal over a wide area with little data on regional treatment trends and outcomes. This investigation was undertaken to evaluate the surgical outcomes of gastric cancer patients presenting to a single upper gastrointestinal centre (WDHB, Waitemata District Health Board) and to compare these to national and international standards. Methods: Data on 135 patients with histologically proven gastric adenocarcinoma presenting between January 2010 and December 2014 were reviewed and compared with nationally available procedural volume data. Results: Sixty of 135 patients were resected (resection rate 44%) and 75 patients were managed with palliative chemotherapy/symptomatic care alone. Twenty‐six patients (43%) received adjuvant or neoadjuvant chemotherapy and only two patients (3%) underwent laparoscopic resection. In resected patients, 90‐day mortality was 1.6%, and 11 patients (18%) developed complications ≥ Clavien‐Dindo grade 3. Fifty‐two patients (87%) had ≥15 lymph nodes resected and 54 patients (90%) had a histological R0 resection. At median follow‐up of 49 months, 30 patients remain alive and disease‐free with 20 true 5‐year disease‐free survivors. National data between 2010 and 2014 showed WDHB performed 20% (338/1710) of gastric resections for all indications in New Zealand. Conclusion: While WDHB is an internationally low volume centre for gastric cancer, surgical outcomes benchmark satisfactorily to international standards. New Zealand's national treatment standards should set aspirational goals for gastric cancer treatment and have a clear strategy to address issues of surgical volume and national service provision. Abstract : New Zealand's national treatment standards should set aspirational goals for gastric cancer treatment and have a clear strategy to address issues of surgical volume and national service provision.